A266 OUTCOMES OF ENDOSCOPIC TREATMENT OF ZENKER'S DIVERTICULUM: EXPERIENCE IN A CANADIAN CENTRE. (15th March 2019) - Kok, B; Zepeda-Gomez, S
Abstract: Background: A common cause of benign dysphagia in adults is Zenker's diverticulum (ZD). Therapeutic options include rigid endoscopy or open surgical approach. These techniques may however be associated with complications such as recurrent nerve palsy and salivary fistula. Furthermore, patients with multiple comorbidities may not be fit for surgery. Treatment with flexible endoscopic diverticulotomy (FED) has been shown to be associated with lower complication rates and shorter hospital stays when compared with surgical approach. Aims: To describe the endoscopic technique and outcomes of FED for the treatment of ZD performed at our centre. Methods: All cases of ZD treated by FED performed from January 2012 to October 2018 were retrospectively reviewed. Patient demographics, comorbidities, pre-procedure symptoms, peri-procedural events and post-procedure outcomes were identified. Subjective improvement of symptoms after endoscopic treatment (dysphagia, regurgitation, choking) was counted as treatment success. Repeat FED procedures on the same patient were counted as distinct events. Results: During the study period, 30 FEDs were performed in 18 patients, 83.3% of the population was male, median age at time of procedure was 71 years (range 49–87 years). All cases of FED were done under sedation by an anesthetist with orotracheal intubation. The procedures were done by a single endoscopist who performed the same endoscopic technique in all cases: CO2 insufflation, prior insertion of an oro-gastric tube and placement of a transparent hood at the scope tip. The cricopharyngeal myotomy was generally performed to 80–90% of the depth of the ZD pouch to maximize prevention of perforation. Nine patients underwent 1 session of FED, 6 patients underwent 2, and 3 patients underwent 3 FEDs. Ninety percent of patients had relief of symptoms after endoscopic treatment. One patient was referred for surgical repair due to recurrence of symptoms. Mild bleeding was reported in 15 cases (50%), this was self-limited in 3 (10%). Injection of adrenaline alone or electrocoagulation alone was required in 2 cases (6.7%), and hemoclip placement in 10 (33.3%). Prophylactic hemoclips were applied at the base of the defect in 4 cases (13.3%). Significant post-procedure pain was experienced in 1 patient (3%) but there was no perforation identified and resolved after 48 hours. With the exception of 1 case (patient was observed overnight for 24 hours), all FED cases were performed as day-case procedures with same day discharge after two hours of observation in recovery. No cases of perforation or other complications were reported. Conclusions: In our experience, FED is a safe and effective treatment modality for symptoms related to ZD. Mild intra-procedural bleeding was common but this was adequately managed by endotherapy. About half of patients may require repeated FED for full symptom resolution. Funding Agencies: None